Interactions of the barley SD1 and SD2 seed dormancy loci influence preharvest sprouting, seed dormancy, and malting quality. Issue 1 (24th November 2021) - Sweeney, Daniel W.; Rooney, Travis E.; Walling, Jason G.; Sorrells, Mark E.
Abstract: Preharvest sprouting (PHS) can severely damage barley ( Hordeum vulgare L.) malting quality and is of particular concern in locations with a high frequency of precipitation around harvest. Malting quality and PHS resistance are often negatively correlated, and the SD2 locus on chromosome 5H has been associated with both traits. Using three spring barley populations, PHS, seed dormancy, and germination rate were mapped over six time points to identify changes in genetic control of these traits during the after‐ripening period. HvAlaAT1 at the SD1 locus was associated with long‐term dormancy and reduced germination rate. Ninety lines were Sanger sequenced for HvGA20ox1, but variants were not associated with PHS or germination traits. The allelic state of HvMKK3 was strongly associated with genetic PHS susceptibility in North American spring two‐row barley germplasm and interactions between HvAlaAT1 and HvMKK3 were associated with changes in seed dormancy and germination rate over time. Several malting quality traits were associated with HvMKK3 alleles. Kompetitive allele‐specific polymerase chain reaction (KASP) markers were developed for the causal mutations in HvAlaAT1 and HvMKK3 and a diagnostic mutation in HvGA20ox1 . Haplotypes with PHS resistance, short primary dormancy, and a high germination rate were identified that could be useful for breeding for PHS resistance and malting quality. Core Ideas: Pleiotropic effects of the SD2 locus in barley are associated with multiple alleles of HvMKK3 . HvGA20ox1 variants had minor to no effect on dormancy or malting quality traits. Dormancy release and germination rate were associated with HvMKK3 and HvAlaAT1 interaction. KASP markers for dormancy genes can support breeding for PHS and malting quality.